Highly electrocatalytic activity and excellent methanol tolerance of hexagonal spinel-type Mn2AlO4 nanosheets towards oxygen reduction reaction: Experiment and density functional theory calculation. (May 2016) - Si, Conghui; Wang, Ying; Zhang, Jie; Gao, Hui; Lv, Lanfen; Han, Lulu; Zhang, Zhonghua
Abstract: Oxygen reduction reaction (ORR) is of crucial importance in fuel cells and metal–air batteries, however, the sluggish dynamics of ORR remains a critical issue to be addressed. Here, we report the preparation of hexagonal spinel-type Mn2 AlO4 nanosheets with a high BET surface area of up to 164 m 2 g −1 through a dealloying–annealing strategy. The Mn2 AlO4 catalyst shows a good catalytic activity towards ORR in the alkaline solution, as well as much better methanol tolerance than the commercial Pt/C. Moreover, both the electrochemical measurements and density functional theory (DFT) calculations (adsorption energy, density of states, H2 O2 decomposition) demonstrate that the ORR on Mn2 AlO4 is a four-electron pathway. In addition, the DFT results expound the reason why the Mn2 AlO4 catalyst has much better methanol tolerance than Pt/C. Graphical abstract: Highlights: Hexagonal spinel-type Mn2 AlO4 nanosheets were fabricated by dealloying/annealing. The Mn2 AlO4 nanosheets exhibit a high BET surface area of up to 164 m 2 g −1 . Mn2 AlO4 nanosheets show superior catalytic activity and methanol tolerance in ORR. The RDE, RRDE and DFT results confirm the 4e − pathway for ORR on Mn2 AlO4 .